Mathematics learning based on the science context: Mathematics learning based on the science context (Revista Electrónica Calidad en la Educación Superior, 2019)
This teaching innovation work aims to promote understanding on fundamental mathematics topics such as equations and functions, through the related sciences contextualization. In addition to strengthening the reflective and intuitive thinking ability, for the context problems resolution through different strategies.The methodology, contextual learning theory REACT was addressed; in four stages: Master class, Case studies design, Cases application in the classroom, Contextual learning evaluation and monitoring. Among the most relevant results, it can be mentioned that 90% increased their interest by the mathematics study. In conclusion, the contextual learning method provides the student with a stronger academic base and facilitates the mathematical concepts understanding that relate to their professional environment.
Keywords: study cases, mathematical education, teaching innovation strategies